Time to treatment in pediatric patients with repeated episodes of status epilepticus - Jennifer V. Gettings; Iván Sánchez Fernández; Anne Anderson; J. Nicholas Brenton; Afra Can; Justice Clark; Raquel Farias Moeller; Howard P. Goodkin; Yi-Chen Lai; Mohamad A. Mikati; Lindsey A. Morgan; Edward Novotny; et al. (BMC Neurology)
Abstract Objective To compare pediatric patients who presented with repeated status epilepticus episodes to patients with a single episode of status epilepticus and identify distinguishing clinical factors. Methods Retrospective analysis of a multicenter, prospective observational cohort of pediatric patients with status epilepticus between 2011 and 2019. Results Out of 504 status epilepticus episodes in 420 patients, 50 patients (10.3%) had repeated episodes of status epilepticus. The only predictor of repeated status epilepticus was a prior diagnosis of epilepsy. There was no difference in time to treatment with the first benzodiazepine in patients presenting with their first status epilepticus episode compared to their second status epilepticus episode [median 10 (interquartile range 5–30) vs. 14 (4.5–52.5) minutes; (p = 0.24)] or in time to treatment with the first non- benzodiazepine anti-seizure medication (ASM) [61 (37–125) vs. 71 (34.5-117.5) minutes; p = 0.61]. In patients with repeated status epilepticus episodes with onset outside the hospital, the percentage of patients treated by caregivers did not improve between the first and second status epilepticus episode (61% vs. 60%, p = 0.56). However, the time to first benzodiazepine was shorter in patients treated by caregivers compared to those who were not [5 (0–25) vs. 55 (41–120) minutes; p < 0.001]. Conclusions Time to treatment with benzodiazepine and non-benzodiazepine ASM in patients with repeated episodes of status epilepticus does not improve for a second episode of status epilepticus, suggesting additional opportunities for intervention and teaching.